1977
DOI: 10.1007/bf01665095
|View full text |Cite
|
Sign up to set email alerts
|

A 44‐year experience with tuberculous enterocolitis

Abstract: Thirty‐one eases of intestinal tuberculosis, diagnosed from 1932 through 1975 at The New York Hospital‐Cornell Medical Center, were reviewed with particular reference to the impact of antituberculous chemotherapy on the outcome of the disease and to the role of surgery in diagnosis and treatment. The chest X‐ray was 90% effective in demonstrating evidence of tuberculosis in this series. However, since even on gross examination differentiation of intestinal tuberculosis from Crohn's disease or neoplasia may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
2

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 8 publications
1
7
2
Order By: Relevance
“…Some workers report that the disease is more common in males in the western countries while in developing counties the females predominate [28]. We could not find in literature the reasons for this gender differences.…”
Section: Discussioncontrasting
confidence: 56%
“…Some workers report that the disease is more common in males in the western countries while in developing counties the females predominate [28]. We could not find in literature the reasons for this gender differences.…”
Section: Discussioncontrasting
confidence: 56%
“…We agree with Homan et al (1977) that 'surgical exploration is indicated in patients in whom the diagnosis is in doubt'. Even when laparotomy has been performed, the ultimate diagnosis may only be achieved after histological and bacteriological study.…”
supporting
confidence: 76%
“…While TBP is a relatively rare type of TB infection in industrialized countries (and thus extremely rare in patients with CSF shunts), it is still a common infection in many regions of the world, and delayed diagnosis or misdiagnosis can be fatal. [2] TBP usually yields lower bacterial counts, and both the clinical and radiological features are nonspecific,[67121626] making it one of the most difficult forms of TB to correctly diagnose. This is especially true in patients without obvious risk factors, such as exposure to TB, cirrhosis, alcoholism, renal failure with peritoneal dialysis, diabetes mellitus, malignancy, immunosuppressive medication (e.g.…”
Section: Discussionmentioning
confidence: 99%